The Nature of Environmental Quality in the Workplace: A Johnson Controls Institute Position Paper - (:unkn) unknown (My University, 1994)
As current research literature on workplace information grows exponentially, it often serves to hinder the larger goal of integrating our efforts into the creation of good workplaces. This monograph argues for a positive model of what the workplace should be, a set of goals, and criteria that can guide the innumerable decisions which go into the creation or remodeling of workplaces.